2016
DOI: 10.1371/journal.pone.0168298
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing the Mechanical Properties of Running-Specific Prostheses

Abstract: The mechanical stiffness of running-specific prostheses likely affects the functional abilities of athletes with leg amputations. However, each prosthetic manufacturer recommends prostheses based on subjective stiffness categories rather than performance based metrics. The actual mechanical stiffness values of running-specific prostheses (i.e. kN/m) are unknown. Consequently, we sought to characterize and disseminate the stiffness values of running-specific prostheses so that researchers, clinicians, and athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(122 citation statements)
references
References 28 publications
4
117
0
1
Order By: Relevance
“…2, it seems that the use of a prosthetic knee and foot results in a large amount of energy loss (hysteresis) in the vGRF-COM displacement curves during ground contact. Therefore, as demonstrated by past findings 7,14,19 , the stiffness of each prosthetic component should be addressed to determine stiffness regulation during running using RSPs. Second, in our study, each participant ran at different f step at a given running speed, which differed depending on the participant.…”
Section: And Prostheticmentioning
confidence: 97%
“…2, it seems that the use of a prosthetic knee and foot results in a large amount of energy loss (hysteresis) in the vGRF-COM displacement curves during ground contact. Therefore, as demonstrated by past findings 7,14,19 , the stiffness of each prosthetic component should be addressed to determine stiffness regulation during running using RSPs. Second, in our study, each participant ran at different f step at a given running speed, which differed depending on the participant.…”
Section: And Prostheticmentioning
confidence: 97%
“…Stiffness curve and damping response is fixed and depends on material properties, shape, and thickness [5,6]. Feet are prescribed to patients in stiffness categories, primarily based on weight and activity levels [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We used the mean AL peak resultant GRFs measured in the current study and the reported RSP stiffness values from each device reported by Beck et al 4 (Supplementary Tables 1, 3 and 4) (k RSP ) to calculate RSP displacement (ΔRSP):…”
mentioning
confidence: 99%